Early Canadian gardening : an 1827 nursery catalogue - Woodhead, Eileen (McGill-Queen's University Press, 1998)
Reproducing a rare 1827 plant and seed catalogue, possibly the earliest extant catalogue of its kind in Canada, Early Canadian Gardening presents an extensive range of garden plants -- trees, shrubs, fruits, and flowers -- that were grown for food, medicines, and dyestuffs as well as ornamental purposes. Eileen Woodhead provides a detailed description and brief history of the cultivation and use of each plant up to the present day. Most of the descriptions are accompanied by detailed drawings by the author, who found and grew many of the original varieties in the catalogue. The book provides a valuable account of the business of horticulture in the first decades of the nineteenth century -- the practices of importers, merchants, farms, and households -- placing it within the broader context of social history. It includes an appendix of historic sites and botanical gardens in Ontario, as well as sources for heritage seeds. Early Canadian Gardening is a ground-breaking account of the practice and significance of horticulture during the period of settlement in Upper Canada and stands as a remarkable work of historical botany. It will be an invaluable source document for horticulturists and botanists, historians, and garden enthusiasts with an interest in heritage plants.